(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Family Conflicts — A Factor with Hidden Influence Usually, arguments between parents are considered a personal matter of adults. However, in reality, every harsh word, disrespectful interaction, or loud dispute leaves a deep mark on a child’s mind. Even though a child cannot understand problems the way adults do, they can sense the tension at home and try to interpret it in their own way. During this process, the child may arrive at incorrect conclusions, feel guilty, or live in fear.